KADVI HAWA TO JAWAAN: HOW INDIAN CINEMA PORTRAYED THE FIGHT AGAINST CLIMATE CHANGE - Das, Rajesh; Banerjee, Ipsita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With its visual storyline, dramatic message design, and plenty of cognitive aspects, cinema is a powerful tool that can sway and inspire viewers. One of the key elements of development communication, such as programmes addressing gender issues, environmental challenges, or public health and hygiene awareness, is persuasive communication. In this regard, the present research has tried to evaluate the role of films as persuasive medium of communication for spreading awareness on climate change. Two films, namely, Kadvi Hawa and Jawan have been selected for this study to identify the portrayal of draught affected farmers and the aftermath of climate change. With the help of narrative analysis, analysing the dialogues and framing analysis the results of the research have been derived. This research has been based on an interpretivism philosophy and a deductive research approach.